The wear mechanism of mill beaters for coal grinding made-up from high manganese cast steel. (December 2022) - Bembenek, Michał; Krawczyk, Janusz; Pańcikiewicz, Krzysztof
Highlights: The presence of carbides indicates an incomplete supersaturation of the material, which also limits wear resistance. The undesirable presence of carbides after the supersaturation process caused the formation of cracks along their precipitations. .The decrease in the content of the alloying elements resulted in intense and high wear. Methodology of material hardening assessment based on HRC measurements in and outside the HBW indentation. Abstract: Determination of the cause-and-effect relationship regarding the wear of the lining (beater) of a coal beater mill is presented. The type and state of the material used for the aforementioned mill element was assessed. The lining wear mechanism was brought to the state of the aforementioned material. In the analyzed case, excessive wear of the Hadfield steel beater of the fan mill was identified. This study analyzes the chemical composition, macro- and microscopic examinations and hardness tests to find the cause of their unsatisfactory wear resistance. The test results show a significant influence of the carbon content on the process of strengthening the surface layer of the beater and the justification for considering the use of various materials for individual elements of the beaters. The methodology of testing the material's ability to deformation hardening was proposed and the role of the manganese cementite mesh in the decohesion (destruction) of the structure as a result of the coincidence of such precipitates with intense deformation micro-twinning has been presented. Analyzed cast steel has a high tendency to strain hardening (from 190 HBW to 500 HBW). As a result of exploitation, investigated plates were highly worn. The primary mechanism of wear was erosion. The presence of carbides in the microstructure also indicates an incomplete supersaturation of the material.